The association of caffeine consumption with positive affect but not with negative affect changes across the day - Justin Hachenberger; Yu-Mei Li; Anu Realo; Sakari Lemola (Scientific Reports)
Abstract Caffeine is well known for its stimulant effects on the central nervous system, leading to enhanced cognitive performance and changes in affective states. While these effects have been extensively studied in controlled laboratory settings, caffeine’s influence on affect in everyday life remains comparatively underexplored. This study aims to bridge this gap by examining the associations between momentary caffeine consumption and affective states in naturalistic settings, while also accounting for potential moderators such as time of the day, individual differences, and contextual factors. Employing an experience sampling methodology (ESM), we analyzed data from 115 participants aged 18–25 in Study 1 and 121 participants aged 18–29 in Study 2. Study 1 lasted 14 days yielding 8335 completed surveys and Study 2 lasted 28 days yielding 19,960 completed surveys. Our findings indicate that caffeine intake was associated with subsequent increases in positive affect, while associations with decreases in negative affect were less consistent. The association between caffeine consumption and positive affect was strongest within the first 2.5 h after awakening (i.e., in the morning). Tiredness and social context moderated this association. Overall, the findings of this ESM study suggest that caffeine may play an important role in modulating affective states in everyday life.